STUDI KELAYAKAN FINANSIAL BISNIS EDIBLE FLOWERS PT IJO KREASI INDONESIA PADA MASA PANDEMI COVID-19 - Radella Adi Putri; Ernah Ernah (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
Edible flowers are the main business commodity at PT Ijo Kreasi Indonesia, Bandung City. The floriculture business has a promising prospect both in the domestic and foreign markets. This can be seen from the growth floriculture enthusiasts from year to year. However, the Covid-19 pandemic affected the edible flowers business because the company's main market were hotels and restaurants, so that during the pandemic there was 50-60% decrease in flowers sales. Therefore, PT Ijo Kreasi Indonesia needs to identify the financial feasibility of the edible flowers business during the pandemic to see the company's prospects in the future. The purpose of this research is to determine whether the business is feasible or not. This study uses a quantitative design with descriptive analysis method. Analysis of the data used is descriptive quantitative analysis that is through the calculation of BEP, NPV, Net B/C, Payback Period, IRR, and sensitivity analysis. The results of this research based on each aspect show positive results that the company has met the business criteria so that are feasible to run and have prospects for the future.